Optimized Bamboo Panels Techniques for Sustainable Lighting And Thermal Solutions - Azka Al Athar; Yulianto Purwono Prihatmaji (Center for Scientific Publication, 2024)
This research aims to explore diverse bamboo processing techniques for panel production and their impact on indoor environmental quality, with a focus on lighting and thermal comfort. By reviewing traditional and contemporary methods of bamboo technique, we identify optimal approaches for creating bamboo panels that enhance natural lighting and thermal conditions. Laboratory testing and simulations are employed to analyze changes in optical properties and thermal performance, including light transmission, diffusion, thermal conductivity, and insulation. The findings provide architects and construction professionals with actionable insights into leveraging bamboo's sustainability to achieve superior indoor environments. This study promotes eco-friendly building practices that prioritize occupant well-being and environmental preservation.